Is sleeve gastrectomy a therapeutic procedure for all obese patients?. (June 2016) - Vuolo, Giuseppe; Voglino, Costantino; Tirone, Andrea; Colasanto, Giuseppina; Gaggelli, Ilaria; Ciuoli, Cristina; Ferrara, Francesco; Marrelli, Daniele
Abstract: Background: Laparoscopic sleeve gastrectomy (LSG) is a worldwide surgical procedure for morbid obesity. However patients selection is still anecdotal. The aim of this study is to analyse clinical and anthropometric parameters correlated with LSG and to check the validity of this procedure for different categories of obese patients. Methods: Two-hundred one consecutive patients were submitted to LSG as a primary bariatric procedure between 2008 and 2014. One year follow-up was completed in 159 patients. Smaller groups of patients completed 2 and 3 years follow-up (78, 46 patients respectively). Median preoperative body mass index (BMI) was 45.4 kg/m2 (range: 34.8–73.8); 135 patients (80%) had one or more comorbidities. Potential correlations between age, gender, preoperative BMI, preoperative excess weight, early excess weight loss (EWL) and 1 and 3 year-EWL were investigated. Results: All procedures were regularly completed with laparoscopic approach without conversion to laparotomy. Postoperative complications occurred in six patients (3.7%); no postoperative mortality was observed. Median one-year BMI and EWL were 32.8 kg/m2 and 55.34%, respectively. Three year-EWL was significantly influenced by age, and early EWL. A complete normalization of glycemic levels after the three-year follow-up was also observed in high percentage of diabetic patients. In patients with preoperative BMI>50 kg/m2 we observed most failure cases in terms of EWL and the worst metabolic results. Conclusions: Our experience indicates that LSG is a safe procedure with satisfactory three-year late weight loss in patients with preoperative BMI <50 kg/m2. Promising results, in terms of improvements of comorbidities, were also observed. These results make LSG one of the most attractive first stage surgical procedure for morbid obesity. Highlights: Laparoscopic sleeve gastrectomy (LSG) is a safe procedure with a limited morbidity risk. Potential benefit of the procedure in patients with preoperative BMI <50 kg/m2. Our results confirm LSG as one of the most attractive first stage surgical procedure for morbid obesity.